1989
DOI: 10.1093/nar/17.13.5339
|View full text |Cite
|
Sign up to set email alerts
|

DNase I sensitivity of immunoglobulin light chain genes in Abelson murine leukemia virus transformed pre-B cell lines

Abstract: We have used Abelson murine leukemia virus (A-MuLV) transformed pre-B cell lines to test the hypothesis that the rearrangement potential of a developing B-lymphocyte is dependent on an "opening" of the chromatin structure surrounding immunoglobulin (Ig) genes, thus allowing accessibility to an Ig gene recombinase.The chromatin structures surrounding heavy (H), kappa (K), and lambda (X) chain constant-region genes were assessed by DNase I sensitivity in A-MuLV transformed cell lines capable of H, K or X gene re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Recombination at immunoglobulin and T-cell receptor loci is likely to be influenced by many factors, including transcription and accessibility (34)(35)(36)(37). The results presented in this paper introduce RSS as a previously underestimated factor affecting recombination frequency.…”
Section: Discussionmentioning
confidence: 79%
“…Recombination at immunoglobulin and T-cell receptor loci is likely to be influenced by many factors, including transcription and accessibility (34)(35)(36)(37). The results presented in this paper introduce RSS as a previously underestimated factor affecting recombination frequency.…”
Section: Discussionmentioning
confidence: 79%
“…The structure of the nucleosome was monitored by DNase I footprinting as a function of transcription and RecA-promoted DNA pairing (Fig. 6) (1,9,19,24). Experiments with transfected plasmid constructs suitable for recombination have also been performed, and the results suggested that the relationship between transcription and recombination in the V(D)J rearrangement events is only temporal (11).…”
Section: Resultsmentioning
confidence: 99%
“…Increases in DNase I sensitivity and alterations in chromatin structure at the Ig locus have been reported to be associated with germline transcription and recombination (35)(36)(37)(38). We measured accessibility of the Ig locus to DNase I during induction of 103X7 cells by real-time PCR using primers for 13 amplicons spanning the Ig locus (Fig.…”
Section: Dnase I Accessibilitymentioning
confidence: 99%